2011
DOI: 10.1111/j.1600-0854.2011.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 and Calmodulin Interactions Modulate Dynamics of ARF6‐Dependent Endocytosis

Abstract: The main cellular Ca 2+ sensor, calmodulin (CaM), interacts with and regulates several small GTPases, including Rac1. The present study revealed high binding affinity of Rac1 for CaM and uncovered two new essential binding domains in Rac1: the polybasic region, important for phosphatidylinositol-4-phosphate 5-kinase (PIP5K) interaction, and the adjacent prenyl group. CaM inhibition increased Rac1 binding to PIP5K and induced an extensive phosphatidylinositol 4,5-bisphosphate (PI4,5P 2 )-positive tubular membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 90 publications
0
40
0
Order By: Relevance
“…Binding appears to be selective for activated, membrane-associated Rac1, since an activated Rac1V12 mutant, lacking the C-terminal prenylation site (Cys 189), did not associate to calmodulin. 73 This interaction of Rac1 and calmodulin is reminiscent of the interaction between calmodulin and K-Ras 4B, which also requires the K-Ras4B HVR. 74 Notably, efficient interaction of K-Ras4B with calmodulin was nucleotidedependent and required the catalytic region of the GTPase.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Binding appears to be selective for activated, membrane-associated Rac1, since an activated Rac1V12 mutant, lacking the C-terminal prenylation site (Cys 189), did not associate to calmodulin. 73 This interaction of Rac1 and calmodulin is reminiscent of the interaction between calmodulin and K-Ras 4B, which also requires the K-Ras4B HVR. 74 Notably, efficient interaction of K-Ras4B with calmodulin was nucleotidedependent and required the catalytic region of the GTPase.…”
mentioning
confidence: 99%
“…A recent study by Vidal-Quadras et al 73 showed that Rac1 binds to calmodulin in a calcium-dependent manner. This interaction required both the PBR in the Rac1 C-terminus, as well as the lipid anchor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the complex containing RhoA and its GEF Syx translocates to the leading edge of migrating cells through a form of exocytosis that is dependent on another GTPase, Rab13. In turn, Rab13 has been shown to have a role in cell signaling through its interaction with growth factor Arf1 and Rac1 Co-activation of the WAVE regulatory complex WAVE-dependent actin-driven bead motility (cell-free assay) (Koronakis et al, 2011) Arf1 and Cdc42 Arf1-dependent regulation of Cdc42 by ARHGAP10 Actin-mediated clathrin-independent endocytosis (Kumari and Mayor, 2008) Arf6 and Cdc42 Arf6-dependent exocytosis of Cdc42 and its GEF b-PIX at the leading edge Actin-driven polarized astrocyte migration (wound-healing assay) (Osmani et al, 2010) Arf6 and Rac1 ARNO-mediated Rac1 activation Fibronectin-induced haptotactic epithelial cell migration (White et al, 2010) Arf6 and Rac1 Rac1-PIP5K-induced Arf6-dependent endocytosis Clathrin-independent plasma membrane invagination and tubulation (Vidal-Quadras et al, 2011) Rab5 and Rac1 Transition from Rac1-PtdIns(3,4,5)P 3 to Rab5a-PtdIns(3)P for macropinocytic cup closure Macropinocytosis in macrophages (Yoshida et al, 2009) Rab13 and RhoA Rab13-dependent translocation of RhoA and its GEF Syx to the leading edge VEGF-mediated endothelial cell migration (Wu et al, 2011) receptors, such as the vascular-endothelial growth factor (VEGF) receptor 2 (Wu et al, 2011) (see Table 1). The accumulation of active Rho GTPases in specific plasma membrane regions also occurs through mechanisms other than exocytosis.…”
Section: Rho Gtpases -Mechanisms Of Action and Localizationmentioning
confidence: 99%
“…During CLIC-mediated endocytosis, actin remodeling is controlled by Cdc42 together with Arf1 (Doherty and Lundmark, 2009;Kumari and Mayor, 2008) (Table 1). By contrast Rac1, together with the Ca 2+ -binding protein calmodulin, has been shown to inhibit this process (Vidal-Quadras et al, 2011).…”
Section: Sculpting Of Membrane Invaginationsmentioning
confidence: 99%